The hypertense aged people and the self-care - Freire, Maria Roberlandia Soares de Melo; Nóbrega, Maria Miriam Lima da (Rev Rene, 2001)
This study had as objective to apply and to evaluate the concepts of the Self-care Deficit Theory of Nursing the Orem in the systematization of the nursing assistance hypertense aged people. The results allowed the identification of the nursing diagnoses, for which the sell-care actions were developed, implemented and appraised. Ending, the importance of the practice’s application of the nursing process to the light of the Orem self-care referential, that facilitated the identification of diagnoses, the planning, the execution and the evaluation of the nursing attendance, seeking to the customer’s placement in the self-care.